(untitled) (Global Journal of Human-Social Science, 2013)
This study examined the correlation and covariance between education mismatch and skills mismatch in the Tanzanian Formal sector taking Dar es Salaam and Dodoma regions as case studies. The study employed cross sectional and Worker Self Assessment (WSA) techniques with 319 workers from public and private sectors selected by multistage cluster sampling. Office interviews were conducted to collect qualitative data using structured questionnaire. The SPSS-16 statistical package was used for data analysis. Using Chi square at 5% level of significance, the results reported an existence of relationship between education mismatch and skills mismatch ( χ 2 =39.57; p=0.00). Using bivariate corre- lation, results portrayed a weak positive correlation between education mismatch and skills mismatch (Cor em,sm =0.241). Also, using bivariate covariance, the results showed a positive co-vary behavior between education mismatch and skills mismatch (Cov em,sm = 0.112). This study therefore concludes that education mismatch and skills mismatch are not perfect substitute. It is thus recommended that the government should not take the existence of National Employment Policy of 2008 and its labour regulatory frameworks as a guarantee of succ- ess. Thus, deliberate efforts should be adopted to force both private and public employers to use the same standards, measures and regulations in recruitment to minimize incidence of mismatch. Also, the government and other labour market actors should avoid using education mismatch as a proxy for skills mismatch, since the two have no a one to one relation